Finite time blow-up for a thin-film equation with initial data at arbitrary energy level - Sun, F.; Liu, Lishan; Wu, Yong Hong (Academic Press, 2018)
© 2017 In this paper, we consider the initial boundary value problem for a class of thin-film equations in R n with a p-Laplace term and a nonlocal source term |u| q-2 u-[Formula presented]? O |u| q-2 udx. We prove that there exist weak solutions for the problem with arbitrarily initial energy that blow up in finite time. We also obtain the upper bounds for the blow-up time.